Cosmological Application in Kaluza-Klein Theory: Generalized Sudden Singularity. Issue 2 (3rd July 2019) - Wanjari, Rupali; Khadekar, G. S.
Abstract: In this paper, we considered the cosmological application by taking G and Λ to be a function of t in Kaluza-Klein cosmology. We use the Taylor's expansion of cosmological function Λ( t ), up to the first order of time t and evaluated the cosmological parameters by using the modified equation of state of the form p = −ρ − f ( ρ ), where f ( ρ ) = αρ . The analytical properties of R ( t ), ρ ( t ) and H ( t ) are investigated and it is observed that from the solutions of the field equations, the generalized sudden singularity occurs at a finite time in the framework of Kaluza-Klein theory of gravitation.